Contestation between Puritan Islam and Kejawen in the Urban Yogyakarta of Indonesia - Muhammad Arifin; Irwan Abdullah; Atik Tri Ratnawati (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
Tensions between Puritan Islam and Kejawen Islam have never been resolved, despite various accommodation efforts. The ongoing contestation of the two traditions in Islam in Yogyakarta is because both always maintain strict cultural boundaries through symbols that represent their respective identities, be it in religious, art, cultural, economic and political practices. This study focuses on three aspects: (1) the form of representation of the contestation between Islam and Tradition (Kejawen) in the city of Yogyakarta; (2) the historical and cultural context which is the basis for the contestation between Islam and tradition; and (3) how the contestation between Islam and the Kejawen tradition is managed by each community in an effort to minimize the occurrence of social conflict between the two. Through these three aspects, this research aims to offer a new perspective in viewing the dialectical relations between Puritan Islam and Javanese (Kejawen) tradition contextually. The contestation between the Islamic tradition and the Kejawen tradition continued because of historical, political and global currents that provided space for both traditions to build their respective cultural identities.